2021
DOI: 10.1001/jamanetworkopen.2021.14904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 25-Year Survival of Women With Estrogen Receptor–Positive/ERBB2-Negative Breast Cancer Treated With and Without Tamoxifen Therapy

Abstract: IMPORTANCE Clinically used breast cancer markers, such as tumor size, tumor grade, progesterone receptor (PR) status, and Ki-67 status, are known to be associated with short-term survival, but the association of these markers with long-term (25-year) survival is unclear. OBJECTIVETo assess the association of clinically used breast cancer markers with long-term survival and treatment benefit among postmenopausal women with lymph node-negative, estrogen receptor [ER]-positive and ERBB2-negative breast cancer who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…This effect was substantially mitigated in the group without hormone treatment. This finding is in line with a recent study by Dar et al (2021) , which found a significant tamoxifen treatment benefit only among patients suffering from lower grade tumors, while no benefit was observed for grade 3 tumors. In summary, we observed strong hints that hormone treatment alleviates the negative effect of menopause, and increases the negative effect of high tumor grade on patient survival.…”
Section: Resultssupporting
confidence: 92%
“…This effect was substantially mitigated in the group without hormone treatment. This finding is in line with a recent study by Dar et al (2021) , which found a significant tamoxifen treatment benefit only among patients suffering from lower grade tumors, while no benefit was observed for grade 3 tumors. In summary, we observed strong hints that hormone treatment alleviates the negative effect of menopause, and increases the negative effect of high tumor grade on patient survival.…”
Section: Resultssupporting
confidence: 92%
“…Shorter recurrence-free survival was also recorded in patients with larger tumor size, patients with regional lymph node metastasis, metastatic cancer and more advanced stage of disease. These findings are in accordance with substantial published evidence supporting the conclusion that an advanced disease stage and its components (higher tumor size, presence of lymph node metastasis and presence of distant organ metastases) are strongly associated with shorter recurrence-free survival in breast cancer [ 57 , 58 , 59 , 60 ]. In univariate survival analysis, patients with higher EORTC-QLQ-C30 scores and better physical activity had a longer time to recurrence than those with lower HRQOL and worse physical activity; however, these associations did not remain significant after adjustment for several confounding factors.…”
Section: Discussionsupporting
confidence: 92%
“…By increasing the sample of our study, the proportion of metastatic breast cancer may be reduced, becoming more representative in accordance with the existing literature [ 57 , 58 , 59 , 60 ]. Lastly, the short-term recurrence rate of our study population is quite high compared to the existing studies [ 57 , 58 , 59 , 60 ]. Accordingly, by increasing the sample of our study, the short-term recurrence rate may be lowered, also becoming more representative and in accordance with the existing literature [ 57 , 58 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations